2009
DOI: 10.1007/s10800-009-9938-7
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments and trends in the electrochemical promotion of catalysis (EPOC)

Abstract: Electrochemical Promotion of Catalysis (EPOC or NEMCA effect) is one of the most exciting discoveries in Electrochemistry with great impact on many catalytic and electrocatalytic processes. According to the words of John O'M. Bockris, EPOC is a triumph, and the latest in a series of advances in electrochemistry which have come about in the last 30 years. It has been shown with more than 80 different catalytic systems that the catalytic activity and selectivity of conductive catalysts deposited on solid electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 103 publications
0
49
0
Order By: Relevance
“…This phenomenon is based on the modification of the catalytic properties of an heterogeneous catalyst by the electrochemical pumping of promoter ions from an electro-active catalyst support, which is a solid electrolyte material. Until now, this phenomenon has been demonstrated in more than 80 catalytic systems with several important technological possibilities, particularly in industrial product selectivity [12,13]. For instance, previous works have demonstrated the interest of EPOC in enhancing the selectivity of several catalytic processes such as the selective catalytic reduction of NO x [14,15], CO 2 hydrogenation [16], Fischer-Tropsch synthesis [17], or CO preferential oxidation [18].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is based on the modification of the catalytic properties of an heterogeneous catalyst by the electrochemical pumping of promoter ions from an electro-active catalyst support, which is a solid electrolyte material. Until now, this phenomenon has been demonstrated in more than 80 catalytic systems with several important technological possibilities, particularly in industrial product selectivity [12,13]. For instance, previous works have demonstrated the interest of EPOC in enhancing the selectivity of several catalytic processes such as the selective catalytic reduction of NO x [14,15], CO 2 hydrogenation [16], Fischer-Tropsch synthesis [17], or CO preferential oxidation [18].…”
Section: Introductionmentioning
confidence: 99%
“…A parallel approach to classical chemical promotion is the electrochemical promotion of catalysis (EPOC) or non-faradaic electrochemical modification of catalytic activity (NEMCA effect) [17][18][19][20][21][22][23][24][25][26] which can be used to promote metal catalyst films, also acting as electrodes which are deposited on solid electrolyte supports. Electrochemical promotion allows for continuous in situ control of the coverage of promoting species (O dÀ , Na d+ , K d+ , H d+ ) on the catalyst surface.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous surface science and electrochemical techniques have shown that EPOC is due to a electrochemically controlled migration (reverse-spillover or backspillover) of promoting ionic species (O 2À in the case of YSZ, TiO 2 and CeO 2 , Na + or K + in the case of b 00 -Al 2 O 3 , H + in the case of Nafion, CZI (CaZr 0.9 In 0.1 O 3Àa ) and BCN18 (Ba 3 Ca 1.18 Nb 1.82 O 9Àa ), etc.) between the ionic or mixed ionic-electronic conductorsupport and the gas exposed catalyst surface, through the catalystgas-electrolyte three phase boundaries (tpb) [17][18][19][20][21][22]. Upon application of a change, DU WR , to the potential, U WR , of the catalyst (working electrode) with respect to a reference electrode, these backspillover species, accompanied by their compensating charge in the metal, migrate to the metal-gas interface, creating an overall neutral double layer, termed effective double layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Despite its importance in EPOC, the nature and the properties of this species are not completely clarified yet, 5 and the detailed mechanism of EPOC is still under debate. [6][7][8][9][10][11] In the following, the term ''spillover oxygen'' refers to oxygen which is formed at the three-phase boundary (TPB) of the solid electrolyte (yttria stabilized zirconia, YSZ), the electrode (platinum, Pt) and the gas phase during anodic polarization and diffuses onto the electrode surface-without making any statement on its chemical and electronical nature.…”
Section: Introductionmentioning
confidence: 99%